Customs Clearance System and their Importance in the International Trade Supply Chain - Aspilcueta Aspilcueta, Ricardo (2017)
The research aims to analyze the regulations and procedures of customs clearance implemented by SUNAT and how it influences the dynamics of the different foreign trade operatos; firstly identifying the operators involved in the logistics chain, custom regimes, customs clearance modalities, to finally identify those customs operations that in some way obstruct the facilitation of international trade, which would have a negative impact on the operations Customs in the foreign trade logistics chain. The research reached a descriptive and correlational level, based on the information obtained from SUNAT and the specialized literature. As a result of the investigation it was possible to determine that it is necessary to carry out the adaptation of certain operational and customs activities of the foreign trade logistics chain since our country is in a frank process of growth and dynamization of this activity.